Cohesin's concatenation of sister DNAs maintains their intertwining. - Farcas, A; Uluocak, P; Helmhart, W; Nasmyth, K (2011)
The contribution of DNA catenation to sister chromatid cohesion is unclear partly because it has never been observed directly within mitotic chromosomes. Differential sedimentation-velocity and gel electrophoresis reveal that sisters of 26 kb circular minichromosomes are held together by catenation as well as by cohesin. The finding that chemical crosslinking of cohesin's three subunit interfaces entraps sister DNAs of circular but not linear minichromosomes implies that cohesin functions using a topological principle. Importantly, cohesin holds both catenated and uncatenated DNAs together in this manner. In the vicinity of centromeres, catenanes are resolved by spindle forces, but linkages mediated directly by cohesin resist these forces even after complete decatenation. Crucially, persistence of catenation after S phase depends on cohesin. We conclude that by retarding Topo II-driven decatenation, cohesin mediates sister chromatid cohesion by an indirect mechanism as well as one involving entrapment of sister DNAs inside its tripartite ring.